New product research and development through an eco-innovation approach : A case study in components needed for approach implementation - Hagman, Frida (My University, 2022)
The megatrend of sustainability has increased the pressure to in all organisational activities, consider the environment as a stakeholder and it has also brought with it a novel eco-innovation approach to be implemented in company innovation efforts. However, what is needed to implement such a novel approach is still unclear. As it has been deemed that the most impactful environmental performance is grown in the stage of research and development (R&D), this study aims to answer what components are needed to implement an eco-innovative product R&D approach in a company. A qualitative study with semi-structured interviews was conducted. Four interviews were carried out with representatives from four different Companies who are currently or have in the past focused on eco-innovative product development. Two of the interviewees represented big sized companies not focused on eco-innovation from founding stages whereas the other two represented smaller sized companies focused on eco-innovation from the founding stages. A thematic analysis was used to analyse the data. The study findings provide knowledge on the three main components needed for implementing an eco-innovative product R&D approach. The components concluded at were a leadership and management approach, an environmental approach as well as a R&D approach. The results show that the leadership and management approach highly dictate how and to what extent the two other approaches cooperate with each other in the company. Different external and internal value drivers were presented that aim to hinder or support the leadership and management approach in implementing an eco-innovative product R&D approach. Additionally, key characteristics needed for a successful company environmental approach were presented through collaboration and innovation-oriented learning. The road to implement an eco-innovative product R&D approach, can be found in aligning the three main components with a desired strategy and elements of continuous improvement. The implementation of an eco-innovative product R&D approach further requires knowledge on company vision, value and culture to succeed.

Kestävän kehityksen megatrendi on lisännyt painetta kaikessa organisaatiotoiminnassa, huomioida ympäristö sidosryhmänä. Tämä on myös synnyttänyt uudenlaisen ekoinnovaatio lähestymistavan, joka on otettava huomioon yritysten innovaatiotoiminnoissa. On kuitenkin vielä epäselvää, mitä tällaisen uuden lähestymistavan toteuttamiseksi tarvitaan. Koska on katsottu, että vaikuttavin ympäristötehokkuus luodaan tutkimus- ja kehitysvaiheessa (T&K), tämän tutkimuksen tarkoituksena on vastata, mitä komponentteja yrityksessä tarvitaan ekoinnovatiivisten tuotteiden T&K lähestymistavan toteuttamiseksi. Tutkielma tehtiin kvalitatiivisena tutkimuksena, ja tiedonkeruun menetelmäksi valittiin puolistrukturoidut haastattelut. Neljä haastattelua tehtiin neljän eri yrityksen edustajan kanssa ja yritykset keskittyvät joko tällä hetkellä tai ovat aiemmin keskittyneet ekoinnovatiiviseen tuotekehitykseen. Kaksi haastatelluista edusti suuria yrityksiä, jotka eivät keskittyneet ekoinnovaatioihin perustamisvaiheesta lähtien, kun taas kaksi muuta edustivat pienempiä yrityksiä, jotka ovat keskittyneet ekoinnovaatioihin perustamisesta alkaen. Tietojen analysointiin käytettiin temaattista analyysia. Tutkimustulokset antavat tietoa kolmesta pääkomponentista, joita tarvitaan ekoinnovatiivisen tuotteen T&K lähestymistavan toteuttamiseen. Nämä ovat johtamisen lähestymistapa, ympäristöaiheinen lähestymistapa sekä T&K lähestymistapa. Tulokset osoittavat, että johtamisen lähestymistapa sanelee laajasti, miten ja missä määrin kaksi muuta lähestymistapaa tekevät yhteistyötä keskenään yrityksessä. Tutkielmassa esiteltiin erilaisia ulkoisia ja sisäisiä arvotekijöitä, joiden tavoitteena on estää tai tukea johtamisen lähestymistapaa ekoinnovatiivisten tuotteiden T&K lähestymistavan täytäntöönpanossa. Lisäksi yrityksen onnistuneen ympäristölähestymistavan edellyttämät keskeiset ominaisuudet esiteltiin yhteistyön ja innovaatiokeskeisen oppimisen kautta. Avain ekoinnovatiivisten tuotteiden T&K lähestymistavan toteuttamiseen löytyy kolmen pääkomponentin mukauttamisesta haluttuun strategiaan ja jatkuvan parantamisen osatekijöihin. Ekoinnovatiivisten tuotteiden T&K lähestymistavan menestyksekäs toteuttaminen edellyttää lisäksi yrityksen visiota, arvoja ja kulttuuria koskevaa tietämystä.
Keywords: eco-innovation, product research and development, innovation management